Interpretation of Article 28J Paragraph (2) of the 1945 Constitution Regarding Interfaith Marriage in Indonesia - Azzahra, Syifa Nabilah; Prahasti Suyaman (International Journal of Integrated Science and Technology, 2024)
The problem of interfaith marriage involves the conflict between religious freedom and religious values and the constitution. Regarding interfaith marriage in Indonesia, Article 28J, Paragraph 2 of the 1945 Constitution highlights that legal restrictions may be placed on an individual's rights and freedoms. This research discusses how to ensure the protection of human rights without neglecting upheld religious values. This study uses a normative juridical analysis method of laws and regulations, legal norms and doctrines as well as previous articles on marriage and human rights. The results of the study found that the right to marriage is qualified as a derogable right (a right that can be restricted) by the 1945 Constitution. Although the right to marry is a human right, its implementation is not liberal and the religious aspect in the understanding of particularism greatly affects the protection and enforcement of human rights, including the right to marry.